Characteristics of take-home fentanyl test strip use and support for drug checking services among people who use heroin in Australia: learnings for an increasingly complex drug market - Rachel Sutherland; Maureen Steele; Craig Rodgers; Edmund Silins; Rosie Gilliver; Amy Peacock; Monica Barratt; Nadine Ezard; Krista J. Siefried; Robert Page; Raimondo Bruno; Phillip Read (Harm Reduction Journal)
Abstract Background This paper examines: (i) the acceptability of, and behavioural outcomes associated with, take-home fentanyl test strips (FTS), and (ii) support for, and preferences regarding, drug checking services among people who use heroin. Methods Data were obtained from 78 people who had used heroin in the past 6 months, recruited from treatment and harm reduction services in Sydney, Australia in 2020–21. Participants were provided with 10 BTNX Rapid Response™ single-use immunoassay FTS and surveyed 4 weeks later. Results Among those who completed the follow-up survey (n = 72), 81% (n = 58) had used at least one FTS by the time of follow-up (median 6 strips). Participants reported high confidence in their ability to use FTS at both baseline (immediately post training) and follow-up. Of those who self-reported a positive FTS result (n = 25), 48% (n = 12) reported using less than they otherwise would have or starting with a smaller amount, and 60% (n = 15) shared this information with peers and/or health professionals. Of those who used FTS and responded, 95% (n = 54/57) reported that they would continue using FTS if they were free to access, and 97% (n = 56/58) would recommend them to their peers. Among those who completed the follow-up survey, the majority (93%; n = 67) reported that they would like to be able to access a drug checking service, preferably via a supervised injecting facility or Needle and Syringe Program. Conclusions Acceptability of FTS and support for drug checking were high among our sample. Multi-instrument approaches to drug checking may form one component of an effective response to the emerging threat of illicitly manufactured synthetic opioids.